(untitled) (Biological Sciences - PJSIR, 2000)
A facile synthesis of fully substituted 1,2,4-triazines (3a-3c) involving the reaction of benzoinhydrazone 1with isothiocyanates followed by alkylation, hydroxymethyiation, aminolysis and hydrazinolysis has been described. The structure of the products has been deduced from their elemental analysis and spectral data (UV, IR, IH-NMR and mass spectra). Antimicrobial screening of some.•products revealed that only the compoun 6 showed marked activity towards Streptomyces.